2019
DOI: 10.2166/wst.2019.056
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient oxidation of chromium (III) with hydrogen peroxide in alkaline medium

Abstract: Many technologies have been proposed to oxidize chromium, such as roasting-water leaching technology and hydrometallurgical methods such as pressure oxidative leaching coupled with oxygen, ozone, permanganate and ferrate, but the problems associated with the high temperature, low overall resource utilization efficiency, high energy consumption, and the environmental pollution, still remain unsolved. This paper focuses on the oxidation process of chromium (III) with hydrogen peroxide (H2O2) in an alkaline mediu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…It is known that E Cr 2 O 7 /Cr 3+ 0 = 1.33 V and E VO 2 + /VO 2+ 0 = 1.00 V; therefore, K 2 Cr 2 O 7 was used to oxidize low-valence vanadium during the leaching process. The Δ G of the main reactions were calculated at 298 K. , The results displayed in Figure show that the Δ G was negative, indicating that the oxidative leaching of low-valence vanadium with K 2 Cr 2 O 7 was feasible.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that E Cr 2 O 7 /Cr 3+ 0 = 1.33 V and E VO 2 + /VO 2+ 0 = 1.00 V; therefore, K 2 Cr 2 O 7 was used to oxidize low-valence vanadium during the leaching process. The Δ G of the main reactions were calculated at 298 K. , The results displayed in Figure show that the Δ G was negative, indicating that the oxidative leaching of low-valence vanadium with K 2 Cr 2 O 7 was feasible.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the main reaction during the oxidative leaching process was between the low valent vanadium and MnO2 like Equation (2) and (3). The T G   of Equation (2) [21,22]. The results showed in Figure 2 showed that the △G was negative which indicated that the reaction of Equations (2) and (3) were easy to happen and the oxidative leaching of vanadium with MnO2 was feasible.…”
Section: Reaction Mechanismmentioning
confidence: 98%
“…The chromium contents of some leather tanning wastewater and Ni-chrome heating wires were potentiometrically determined using the proposed paper and ceramic based sensors under batch and hydrodynamic (FIA) modes of measurements. The samples were acidified with dilute HCl, followed by oxidation with alkaline hydrogen peroxide (30%) to convert Cr(III) into Cr(VI) (Equation (4)) [37] before assessment of the total chromium [Cr(III) + Cr(VI)] by the proposed sensors. Parallel runs were performed using flame atomic absorption spectrometry for comparison.…”
Section: Determination Of Chromium In Some Environmental and Industrimentioning
confidence: 99%